Η διδασκαλία Παγκόσμιων Μουσικών Πολιτισμών στο Ελληνικό Δημοτικό Σχολείο. Απόψεις των Σχολικών Συμβούλων Μουσικής - Παπαγεωργίου, Παναγιώτα; Κουτρούμπα, Κωνσταντίνα (Education Sciences, 2014)
In this article we examine the views of School Advisors for Music Education on the implementation of a multilingual perspective in Greek music education, and in particular the teaching of world music cultures in elementary school. The article focuses on how the Advisors perceive the meaning, value and significance of multicultural music education and on the extent to which they consider the teaching of world musics necessary in today. The data were mainly collected through semi-structured interviews and classified into categories in accordance with the method of content analysis. The results indicate that the inclusion of world music cultures in the music classroom has become absolutely necessary for music education in our country, since the multiple benefits that this teaching model can yield seem today highly significant, mainly because of the cultural diversity now prevailing in Greek schools and society, as also around the world.